Agricultural Modernization and Internal Migration in ‎Turkey, 1950-1980: A World Systems Analysis of ‎International Policy Interventions - Celiktas, Mehmet Halid; Özveren, Mustafa; balcioglu, yavuz Selim; Bayraktar, Umit (International Journal of Accounting and Economics Studies, 2025)
This study examines how international developments between 1950 and 1980 fundamentally shaped internal migration dy-‎dynamics in Turkey through the systematic restructuring of rural economic organization. While migration literature typicallyphasizes domestic factors such as agricultural mechanization, land fragmentation, rapid population growth, and regional ine-‎qualities, this research shows that these internal dynamics emerged from Turkey’s structured integration into the global capitalist system through coordinated international policy interventions. Using Immanuel Wallerstein’s World Systems Theory as ‎the analytical framework, the study illustrates how the Truman Doctrine, Marshall Plan, NATO membership, European labor ‎migration, import substitution industrialization, the petroleum crises, the Cyprus Peace Operation, and the January 24 economic-‎ic decisions collectively created institutional arrangements that transformed Turkish agriculture and generated large-scale ru-‎rural-to-urban migration. The research employs a mixed-methods design combining qualitative historical analysis of the 1950–‎‎1980 period with quantitative examination of agricultural transformation indicators from 1961–1980. Primary sources include ‎declassified Foreign Relations of the United States documents that reveal how American policymakers conceptualized Turkish ‎development, while quantitative data from the Food and Agriculture Organization capture shifts in fertilizer use, land distribution, and livestock composition. This temporal structure reflects both data availability and the historical sequence in which international interventions of the 1950s produced measurable agricultural outcomes in later decades. Quantitative findings indicate dramatic agricultural restructuring during 1961–1980. Fertilizer consumption increased nearly tenfold from seventy-five ‎thousand metric tons to more than eight hundred thousand tons, demonstrating capital intensification that reduced labor ‎needs. Arable land grew by eleven percent while permanent meadows and pastures declined twelve percent, showing the conversion of common grazing areas into private croplands that eroded livelihood options for smallholders and landless house-‎holds. Livestock composition also shifted: cattle rose by twenty-six percent and sheep by thirty-three percent, whereas goats declined ‎by twenty-three percent, reflecting policy biases against traditional extensive systems. These structural transformations reduced ‎rural employment while expanding agricultural production for domestic and export markets‎.